Education in daily life activities as fundamental care in heart surgery rehabilitation: a multifactorial approach to the patient and caregiver. (29th July 2021) - Acqualagna, R; Mazzariol, E; Bernardi, P; Feltrin, C
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Education represents Fundamental Nursing Care that responds to a psycho-social need of the patient. Acute Coronary Syndrome and cardiac surgery have a strong impact from a psycho-emotional point of view and in the approach to daily activities after discharge: nursing care in this phase aims to obtain not only the full physical recovery of the person but above all to restore awareness of what will be the repercussions in everyday life. Therefore, it is necessary to develop a path that actively involves the client and the caregiver and that aims to recognize and analyse his potential and finally satisfy his educational needs to guarantee a person"s return home that is consistent with his expectations. PURPOSE: identify the best nursing strategies in managing the educational need of the cardiac surgery patient in the rehabilitation phase involving the caregiver, and describe what aspects to be considered as priorities in personalizing care. METHODS: a narrative literature review. RESULTS: 23 articles were included in the analysis. The literature has shown that the educational need in cardiac surgery patients in the rehabilitation phase can be detected through semi-structured interviews or self-report questionnaires and should be continued even after discharge. Once shared objectives were set with the client, the care process proved to be more effective with the active involvement of the caregiver, who also has educational and information needs that ensure a return to daily life activities and early recognition of any relapses. Furthermore, both for the client and for the caregiver, the literature emphasizes how the consideration of socio-economic, cultural and gender aspects are important in structuring the educational plan: if not considered, feelings of discomfort and frustration can emerge in the people involved and lead to further emotional problems that can compromise the complete recovery of the person. At the base of the path, however, relational competence is essential for the achievement of health objectives, in a continuum of care between hospital and territory. CONCLUSION: The educational path of the person after cardiac surgery represents a central point of fundamental nursing care, even after discharge. Given the need to monitor the achievement of the objectives set, the use of nursing taxonomies could prove useful for this purpose in guaranteeing a timely verification of the educational path both before and after discharge: through the declination of objectives and diversified interventions for patient and caregiver, nurses can share the progress made in the care team and facilitate the transfer of care information between professionals in different settings.